Entrepreneurial strategy : emerging businesses in declining industries - Cassia, Lucio; Fattore, Michael; Paleari, Stefano (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2006)
"Entrepreneurial Strategy" aims to revive the debate on the role of entrepreneurship in the context of mature business. The authors contend that mature and declining industries are increasingly dominated by the negative pressure of external factors, but they are also embedded with a potential renewed role for entrepreneurship because the industry forces as a whole tend to break up, leaving space for strategic business innovation.
Includes bibliographical references (p. 275-289) and index.
rpm 07/09/16
Loans
Keywords: Strategic planning; Industrial management; Entrepreneurship; Entrepreneurial strategy